Conference Proceedings of 2021 International Joint Conference on Energy, Electrical and Power Engineering Power Electronics, Energy Storage and System Control in Energy and Electrical Power Systems - Hu, Cungang; Cao, Wenping; Zhang, Pinjia; Zhang, Zhenbin; Tang, Xi (Lecture Notes in Electrical Engineering, 2022)
X, 763 p. 449 illus., 303 illus. in color.